Getting started with 3d printing : a hands-on guide to the hardware, software, and services behind the new manufacturing revolution - Kloski, Liza Wallach; Kloski, Nick (Maker Media, Inc., 2016)
Make: Getting Started with 3D Printing is a practical, informative, and inspiring book that guides readers step-by-step through understanding how this new technology will empower them to take full advantage of all it has to offer. The book includes fundamental topics such as a short history of 3D printing, the best hardware and software choices for consumers, hands-on tutorial exercises the reader can practice for free at home, and how to apply 3D printing in the readers' life and profession. For every maker or would-be maker who is interested, or is confused, or who wants to get started in 3D printing today, this book offers methodical information that can be read, digested, and put into practice immediately!